The Role of Omega-3 Polyunsaturated Fatty Acids in Patients with Metabolic Syndrome and Endothelial Dysfunction - Andrej Dzupina; Dominik Pella; Pavol Zenuch; Zuzana Zenuchova; Jaipaul Singh; Monika Jankajova; Jan Fedacko (Medicina)
Background and Objectives: Metabolic syndrome (MS) represents several diseases encompassing a heterogeneous group of biochemical and physiological abnormalities characterized by structural and functional alterations in the myocardium, including the endothelium of the coronary arteries. MS also affects a substantial portion of the global population. Understanding the risk factors, the development and treatment associated with MS are of paramount importance for early identification, treatment and prevention. This study was designed to evaluate the role of the supplementation of omega-3 polyunsaturated fatty acids (n-3 PUFAs) on endothelial function in patients with MS. Materials and Methods: A total of 80 patients with MS were enrolled in two groups. The study evaluated endothelial function (EF) in subjects before and after a three-month treatment with n-3 PUFAs in a dose of 2.4 g daily (800 mg, three times a day) vs. placebo, using an Endo-PAT2000 device (Itamar Medical Ltd., Caesarea, Israel) measuring the reactive hyperemia index (a parameter of EF) and augmentation index (a parameter of arterial stiffness). Plasmatic levels of glutathione peroxidase, homocysteine, apolipoprotein B and lipoprotein were also evaluated for comparison. Results: The results showed that the average value of reactive hyperemia index before the treatment with n-3 PUFAs was 1.62 ± 0.42, compared to 1.96 ± 0.62 at the end of the study (p < 0.005). The augmentation index changed from 14.66 ± 19.55 to 9.21 ± 15.64 after the treatment (p = 0.003) with n-3 PUFA. The results also revealed a statistically significant decrease in apolipoprotein B (0.94 ± 0.36 vs. 1.13 ± 0.35, p = 0.001) and homocysteine (19.31 ± 5.29 vs. 13.78 ± 3.05, p = 0.001) and an increase in glutathione peroxidase plasma levels (41.65 ± 8.90 vs. 45.20 ± 8.01), p = 0.001. Conclusions: The results of this prospective study showed a significant improvement in EF in subjects with MS treated with n-3 PUFAs in a dose of 2.4 g daily.